Applying a nanoparticle@mof interface to activate an unconventional regioselectivity of an inert reaction at ambient conditions - Lee, Hiang Kwee (2021)
Here we design an interface between a metal nanoparticle (NP) and a metal-organic framework (MOF) to activate an inert CO₂ carboxylation reaction and in situ monitor its unconventional regioselectivity at the molecular level. Using a Kolbe-Schmitt reaction as model, our strategy exploits the NP@MOF interface to create a pseudo high-pressure CO₂ microenvironment over the phenolic substrate to drive its direct C-H carboxylation at ambient conditions. Conversely, Kolbe-Schmitt reactions usually demand high reaction temperature (>125 °C) and pressure (>80 atm). Notably, we observe an unprecedented CO₂ meta-carboxylation of an arene that was previously deemed impossible in traditional Kolbe-Schmitt reactions. While the phenolic substrate in this study is fixed at the NP@MOF interface to facilitate spectroscopic investigations, free reactants could be activated the same way by the local pressurized CO₂ microenvironment. These valuable insights create enormous opportunities in diverse applications including synthetic chemistry, gas valorization, and greenhouse gas remediation.